Immunocytochemistry Streptavidin Biotin: Early Detection of Viral Nervous Necrosis Virus in the mucous of the Ikan Kerapu Macan(Epinephelus fuscoguttatus) - Putu Eka Sudaryatma; Artanti Tri Lestari; Ni Luh Sunarsih; Ketut Sri Widiarti; Sulis NurHidayah; Didik Srinoto Srinoto (Fakultas Kedokteran Hewan Universitas Gadjah Mada bekerjasama dengan PB PDHI, 2012)
Kerapu macan (Epinephelus fuscoguttatus) is one of the kerapu fishes that has been successfully bred by the farmers. The survival rate of the fish reaches up to the 40% at the fish hatchery of the home industry of in Bali. The disease in which may cause significant mortality in kerapu fish, especially for the larvae and juveniles is viral nervous necrosis (VNN). We therefore developed and applied the immunological diagnostic approach of immunocytochemistry technique of streptavidin biotin (SB) for early detection of VNN. Mucous samples of VNN infected- kerapu fish in vivo were firstly detected by reverse transcriptase-polymerase chain reaction (R T -PCR) for the presence of DNA VNN. If it is RT -PCR-positive VNN, the mucous samples were then tested by SB. Results of the present study indicated that the VNN virus could be detected with SB technique within only 24 hours post infection. It was concluded that rapid and accurate SB technique is suitable and appropriate to be applied for routine control and prevention national program in the Fish Quarantine for Indonesia because no need of fish sacrification, and scientific, law and international accepted, and even no hazardous environmental contamination.Keywords: kerapu macan (Epinephelus fuscoguttatus),VNN, mucous, SB, early detection